Low-temperature anti-freezing coal mine paste filling material and preparation method thereof

CN122977807APending Publication Date: 2026-10-27SHANDONG KANGER ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611246539.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]为解决上述技术问题,本发明提供了一种低温抗冻煤矿膏体充填材料及其制备方法,解决的技术问题是:现有煤矿膏体充填材料低温适应性差、低温易开裂,导致长期支护稳定性不足

Benefits of technology

突破现有低温充填材料依赖防冻剂、低温易收缩开裂、密实度不足的行业局限,采用硫铝酸盐复合低温活性胶凝体系,搭配微量活化助剂,依托矿井水原位离子激发,膏体浆料无离析、无泌水,流动性优异,适配长距离、高扬程井下泵送,在无外源防冻剂的前提下实现0-10℃低温快速硬化,后期通过二次水化反应强度持续增长,抗冻、抗渗、抗变形性能远优于常规充填材料,适配各类复杂矿井工况。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention relates to the field of paste filling materials technology, specifically to a low-temperature frost-resistant paste filling material for coal mines and its preparation method. The low-temperature frost-resistant paste filling material for coal mines is characterized by being prepared from the following raw materials in parts by weight: 35-45 parts modified coal gangue coarse aggregate, 18-25 parts activated fly ash powder, 8-12 parts slag ultrafine powder, 10-15 parts low-temperature active composite cementitious material, 4-7 parts dense frost-resistant modifying component, 20-28 parts mine water, and 0 parts trace activation additive. With a density of 0.3-0.8 parts, this material overcomes the industry limitations of existing low-temperature filling materials, which rely on antifreeze, are prone to shrinkage and cracking at low temperatures, and have insufficient density. It adopts a sulfoaluminate composite low-temperature active gelling system, combined with trace amounts of activating agents, and relies on in-situ ion activation by mine water. The paste slurry has no segregation or bleeding, and has excellent fluidity, making it suitable for long-distance, high-lift underground pumping. Its strength continues to increase through secondary hydration reaction, and its antifreeze, anti-seepage, and anti-deformation properties are far superior to conventional filling materials, making it suitable for various complex mine working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of paste filling materials technology, specifically to a low-temperature resistant paste filling material for coal mines and its preparation method. Background Technology

[0002] Paste backfilling mining is a core technology for achieving green coal mining, mining under coal seams, and managing goaf subsidence. By mixing binders, solid waste aggregates, and water to form a paste, which is then pumped into underground goaf areas, it can effectively control roof subsidence and dispose of coal-based solid waste, offering multiple advantages in safety, environmental protection, and economy. Currently, existing coal mine paste backfilling materials mostly use coal gangue, fly ash, and ordinary Portland cement as core raw materials, achieving strength formation through a single cementitious hydration reaction. The technical system focuses on solid waste blending optimization, single retarding / early strength modification, and conventional room temperature strength enhancement, and related patents and research are approaching saturation.

[0003] Existing filling materials and technologies face two major unresolved common industry challenges, for which there are no targeted composite solutions: First, they are poorly adaptable to working conditions in high-altitude and cold mining areas and deep, low-temperature roadways (ambient temperatures of 0℃-10℃). Conventional pastes exhibit stagnant hydration and slow hardening at low temperatures, resulting in extremely low early strength and susceptibility to problems such as frost heave cracking, loose filling material, and roof support failure. Existing antifreeze modifications largely rely on exogenous antifreeze agents, which are costly, suffer from later strength degradation, and pollute the mine water environment. Second, existing materials are mostly mixed with clean water, failing to fully utilize mine wastewater, resulting in low solid waste activation efficiency, insufficient material density, and susceptibility to cracking and weak impermeability and antifreeze performance under low-temperature freeze-thaw conditions. Single-function modifications cannot simultaneously meet the multiple requirements of pumpable fluidity, rapid low-temperature hardening, and long-term antifreeze stability. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a low-temperature resistant coal mine paste filling material and its preparation method. The technical problem solved is that existing coal mine paste filling materials have poor low-temperature adaptability and are prone to cracking at low temperatures, leading to insufficient long-term support stability. The technical solution adopted by this invention to solve the above technical problems is as follows: 1. A low-temperature resistant coal mine paste filling material, characterized in that it is prepared from the following raw materials in parts by weight: 35-45 parts modified coal gangue coarse aggregate, 18-25 parts activated fly ash powder, 8-12 parts slag ultrafine powder, 10-15 parts low-temperature active composite cementitious material, 4-7 parts dense and freeze-resistant modifying component, 20-28 parts mine water, and 0.3-0.8 parts trace activation additive; The low-temperature active composite cementitious material is composed of ordinary early-strength sulfoaluminate cement, ordinary diatomaceous earth powder, and quicklime powder in a mass ratio of (4.5-5.6):(1.5-2.6):(0.5-1.5). The dense, antifreeze modified component is composed of ultrafine filled powder and micro-expansion stabilizing powder in a mass ratio of (2.5-3.7):(1.4-2.5). The ultrafine filled powder is composed of ordinary metakaolin, anhydrous gypsum, and heavy calcium carbonate powder in a mass ratio of (3.4-4.5):(2.5-3.6):(1.5-2.5), with a particle size of 30-60 μm. The micro-expansion stabilizing powder is composed of ordinary calcined vermiculite powder and industrial porous diatomaceous earth powder, with a particle size of 80-120 μm. The trace activation aid is a compound of industrial anhydrous sodium sulfate and ordinary triethanolamine in a mass ratio of (3.5-4.5):(0.5-1.5). The mine water is raw mine wastewater from underground coal mines, which is used after being filtered to remove solid impurities.

[0005] Furthermore, the preparation method of the modified coal gangue coarse aggregate is as follows: the coal gangue from the coal mine is crushed and screened, and coarse particles with a particle size of 5-15mm are selected. After being calcined at a low temperature of 280-320℃ for 1.2-1.8h, it is naturally cooled to obtain porous active coal gangue aggregate.

[0006] Furthermore, the activated fly ash powder is obtained by mechanically grinding and activating power plant fly ash, and then sieving it to 380-420 mesh.

[0007] A method for preparing a low-temperature resistant coal mine paste filling material, characterized by comprising the following steps: S1. Filter the raw mine water to remove suspended coal slime and solid impurities, and set aside for later use; put the modified coal gangue coarse aggregate, activated fly ash micro powder, and slag ultrafine powder into a dry powder mixer and dry mix for 3-5 minutes to obtain solid waste dry powder mixture. S2. Add the low-temperature active composite gelling agent and trace activation agent to the solid waste dry powder mixture and stir to obtain a uniform composite powder. S3. Evenly sprinkle the dense antifreeze modified component into the composite powder, stir at low speed for a predetermined time, and retain the complete structure of the functional component. S4. Add pretreated mine water to the mixed powder at a uniform speed and stir at high speed for 6-8 minutes to make a uniform paste slurry with a slump of 180-220mm. S5. Pump the paste slurry into the goaf and let it sit naturally for curing.

[0008] Furthermore, in step S4, the stirring speed is 800-1000 r / min.

[0009] Furthermore, in step S3, the low-speed stirring speed is 200-300 r / min, and the stirring time is 2-4 min.

[0010] The beneficial effects of this invention are as follows: Breaking through the industry limitations of existing low-temperature filling materials, such as reliance on antifreeze, easy shrinkage and cracking at low temperatures, and insufficient density, this product adopts a sulfoaluminate composite low-temperature active gelling system, combined with trace amounts of activating agents. Relying on in-situ ion activation by mine water, the paste slurry has no segregation or bleeding, excellent fluidity, and is suitable for long-distance, high-lift underground pumping. It achieves rapid hardening at low temperatures of 0-10℃ without the need for external antifreeze. The strength continues to increase through secondary hydration reaction. Its antifreeze, anti-permeability, and anti-deformation properties are far superior to conventional filling materials, making it suitable for various complex mine working conditions. Detailed Implementation

[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is further described in detail below with reference to the following embodiments, so that the public can better understand the implementation method of this invention. The specific implementation scheme of this invention is as follows: A low-temperature frost-resistant coal mine paste filling material, characterized in that it is prepared from the following raw materials in parts by weight: 35-45 parts of modified coal gangue coarse aggregate, 18-25 parts of activated fly ash micro powder, 8-12 parts of slag ultrafine powder, 10-15 parts of low-temperature active composite cementitious material, 4-7 parts of dense frost-resistant modified component, 20-28 parts of mine water, and 0.3-0.8 parts of trace activation additive.

[0012] The following table lists the raw material weight ratios for seven sets of examples:

[0013] It should be noted that the low-temperature active composite cementitious material is composed of ordinary early-strength sulfoaluminate cement, ordinary diatomaceous earth powder, and quicklime powder in a mass ratio of 4.5:1.5:0.5; in other embodiments, the low-temperature active composite cementitious material is composed of ordinary early-strength sulfoaluminate cement, ordinary diatomaceous earth powder, and quicklime powder in a mass ratio of 5:2:1, 5.5:2.5:1.5, or 5.6:2.6:1.5.

[0014] It should be noted that the dense antifreeze modified component is composed of ultrafine filled micro powder and micro-expansion stabilizing powder in a mass ratio of 2.5:1.5, 3:2, 3.5:2.5, or 3.7:2.5.

[0015] Specifically, the ultrafine filler powder is composed of ordinary metakaolin, anhydrous gypsum, and heavy calcium carbonate powder in a mass ratio of 3.4:2.5:1.5, 4:3:2, 4.5:3.6:2.5, or 3.5:2.5:1.5, with a particle size of 30 μm. In other embodiments, the particle size can also be 40 μm, 50 μm, or 60 μm. The micro-expansion stabilizing powder is composed of ordinary calcined vermiculite powder and industrial porous diatomaceous earth powder, with a particle size of 80 μm. In other embodiments, the particle size can also be 90 μm, 100 μm, 110 μm, or 120 μm.

[0016] The trace activating agent is a compound of industrial anhydrous sodium sulfate and ordinary triethanolamine in a mass ratio of 3.5:0.5 or 4.5:1.5.

[0017] The mine water is raw mine wastewater from underground coal mines, which is used directly after being filtered through a 100-mesh filter to remove solid impurities.

[0018] It should be noted that the preparation method of the modified coal gangue coarse aggregate is as follows: the coal gangue from the coal mine is crushed and screened, and coarse particles with a particle size of 5mm, 10mm or 15mm are selected. After being calcined at a low temperature of 280℃, 290℃, 300℃, 310℃ or 320℃ for 1.2 or 1.8 hours, it is naturally cooled to obtain porous active coal gangue aggregate.

[0019] It should be noted that the activated fly ash powder is obtained by mechanically grinding and activating power plant fly ash, and then sieving it to 380-420 mesh.

[0020] Comparative Example 1: Conventional ordinary silicate cement filling material, without low-temperature composite cementitious material or dense antifreeze modified component, mixed with water, with the following specific weight ratio: 40 parts modified coal gangue coarse aggregate, 22 parts activated fly ash powder, 10 parts slag ultrafine powder, 12 parts ordinary silicate cement, 25 parts water, and 0.5 parts trace activation agent.

[0021] Comparative Example 2: Conventional single-powder modified filling material, without the dense antifreeze modified component of the composite ratio of the present invention, only using ordinary single filling powder as a substitute, the other raw materials, precise ratio, and preparation process are consistent with Example 4 of the present invention to ensure single variable control, the specific weight ratio is as follows: 41 parts modified coal gangue coarse aggregate, 22 parts activated fly ash micro powder, 10 parts slag ultrafine powder, 12 parts low temperature active composite cementitious material, 6 parts ordinary heavy calcium carbonate micro powder, 25 parts mine water, and 0.5 parts trace activation agent.

[0022] Comparative Example 3: Existing low-temperature modified backfill material, using water mixing + conventional exogenous antifreeze, abandoning the in-situ activation process of mine water, without dense antifreeze modification components, is the mainstream modified formula for low-temperature backfill in high-altitude and cold mining areas. The specific weight ratio is: 41 parts modified coal gangue coarse aggregate, 22 parts activated fly ash micro powder, 10 parts slag ultrafine powder, 12 parts low-temperature active composite cementitious material, 25 parts water, 1.0 part conventional antifreeze agent, and 0.5 parts trace activation additive.

[0023] All samples were cured at a low temperature of 0-10℃. The test results of various performance indicators are shown in the table below:

[0024] The embodiments of this invention, in all proportion ranges, can achieve rapid solidification and hardening in a low-temperature environment of 0-10℃. The initial setting time is stable at 3.2-4.0h and the final setting time is stable at 7.2-8.0h. The curing rate is uniform and controllable, which is far superior to existing conventional filling materials. It completely solves the problem of low-temperature hydration stagnation and slow hardening of conventional filling materials. No external antifreeze is required, and there is no risk of strength reduction throughout the process.

[0025] All embodiments exhibited a 7-day compressive strength ≥3.5MPa and a 28-day compressive strength ≥8.0MPa, fully meeting the strength standards for backfilling and support in deep wells and cold mining areas. Furthermore, with the optimization of solid waste ratio and the reasonable addition of functional components, the strength steadily improved, demonstrating excellent structural stability.

[0026] This invention adds a dense, antifreeze modified component, which can achieve an overall density of over 98% in the filling material after 28 days. This effectively seals the internal capillary pores and blocks the channels for moisture intrusion during low-temperature freeze-thaw cycles. At the same time, the micro-expansion component can offset the volume shrinkage during low-temperature hardening, thus avoiding low-temperature cracking and frost heave peeling problems from the root. Its long-term antifreeze stability is far superior to that of conventional filling materials.

[0027] All embodiments maintain a slump of 180-220mm, with no segregation or bleeding, making them suitable for long-distance pumping construction underground; their freeze resistance level far exceeds that of existing conventional materials, allowing them to withstand long-term low-temperature freeze-thaw cycles, making them suitable for year-round construction in cold-climate mines.

[0028] All embodiments utilize large quantities of coal gangue, fly ash, and slag coal-based solid waste, and make on-site use of mine wastewater to replace clean water and exogenous activators. Compared with Comparative Example 3, material costs are significantly reduced, and the green and environmentally friendly advantages are prominent.

[0029] In summary, the low-temperature rapid hardening and high-density antifreeze integrated filling system formed by compounding conventional and readily available raw materials in this invention has significant technological progress and practicality compared with the prior art.

[0030] A method for preparing a low-temperature resistant coal mine paste filling material, characterized by comprising the following steps: S1. Raw material pretreatment: Filter the raw mine water through a 100-mesh filter to remove suspended coal slime and solid impurities, and set aside for later use; put the modified coal gangue coarse aggregate, activated fly ash micro powder, and slag ultrafine powder into a dry powder mixer and dry mix for 3-5 minutes (e.g., 3 minutes, 4 minutes, 5 minutes) to obtain solid waste dry powder mixture. S2. Low-temperature gelling system composite: Add low-temperature active composite gelling material and trace activation aid to solid waste dry powder mixture, dry mix for 2 minutes to obtain uniform composite powder. S3. Functional component modification: The dense antifreeze modification component is evenly sprinkled into the composite powder and stirred at low speed for 1 minute to retain the complete structure of the functional component. S4. Paste mixing: Add pretreated mine water to the mixed powder at a uniform speed and stir at high speed for 6-8 minutes (e.g., 6 minutes, 7 minutes, 8 minutes) to make a uniform paste slurry with a slump of 180-220 mm (e.g., 180 mm, 190 mm, 200 mm, 210 mm, 220 mm). S5. Filling and curing: Pump the paste slurry into the goaf and let it stand naturally for curing. It will initially set in 4 hours and finally set in 8 hours at 0-10℃ (e.g., 0℃, 5℃, 10℃). The compressive strength at 7 days is ≥3.5MPa and the compressive strength at 28 days is ≥8.0MPa.

[0031] Specifically, in step S4, the stirring speed is 800-1000 r / min (e.g., 800 r / min, 900 r / min, 1000 r / min).

[0032] Specifically, in step S3, the low-speed stirring speed is 200-300 r / min (e.g., 200 r / min, 250 r / min, 300 r / min), and the stirring time is 2-4 min (e.g., 2 min, 3 min, 4 min).

Claims

1. A low-temperature resistant, freeze-resistant paste filling material for coal mines, characterized in that, Prepared from the following raw materials in parts by weight: 35-45 parts modified coal gangue coarse aggregate, 18-25 parts activated fly ash powder, 8-12 parts slag ultrafine powder, 10-15 parts low-temperature active composite cementitious material, 4-7 parts dense and freeze-resistant modifying component, 20-28 parts mine water, and 0.3-0.8 parts trace activation additive; The low-temperature active composite cementitious material is composed of ordinary early-strength sulfoaluminate cement, ordinary diatomaceous earth powder, and quicklime powder in a mass ratio of (4.5-5.6):(1.5-2.6):(0.5-1.5). The dense, antifreeze modified component is composed of ultrafine filled powder and micro-expansion stabilizing powder in a mass ratio of (2.5-3.7):(1.4-2.5). The ultrafine filled powder is composed of ordinary metakaolin, anhydrous gypsum, and heavy calcium carbonate powder in a mass ratio of (3.4-4.5):(2.5-3.6):(1.5-2.5), with a particle size of 30-60 μm. The micro-expansion stabilizing powder is composed of ordinary calcined vermiculite powder and industrial porous diatomaceous earth powder, with a particle size of 80-120 μm. The trace activation aid is a compound of industrial anhydrous sodium sulfate and ordinary triethanolamine in a mass ratio of (3.5-4.5):(0.5-1.5). The mine water is raw mine wastewater from underground coal mines, which is used after being filtered to remove solid impurities.

2. The low-temperature resistant coal mine paste filling material according to claim 1, characterized in that, The method for preparing the modified coal gangue coarse aggregate is as follows: the coal gangue from the coal mine is crushed and screened, and coarse particles with a particle size of 5-15mm are selected. After being calcined at a low temperature of 280-320℃ for 1.2-1.8h, the mixture is naturally cooled to obtain porous active coal gangue aggregate.

3. The low-temperature resistant coal mine paste filling material according to claim 1, characterized in that, The activated fly ash powder is obtained by mechanically grinding and activating power plant fly ash, and then sieving it to 380-420 mesh.

4. A method for preparing a low-temperature frost-resistant coal mine paste filling material according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Filter the raw mine water to remove suspended coal slime and solid impurities, and set aside for later use; put the modified coal gangue coarse aggregate, activated fly ash micro powder, and slag ultrafine powder into a dry powder mixer and dry mix for 3-5 minutes to obtain solid waste dry powder mixture. S2. Add the low-temperature active composite gelling agent and trace activation agent to the solid waste dry powder mixture and stir to obtain a uniform composite powder. S3. Evenly sprinkle the dense antifreeze modified component into the composite powder, stir at low speed for a predetermined time, and retain the complete structure of the functional component. S4. Add pretreated mine water to the mixed powder at a uniform speed and stir at high speed for 6-8 minutes to make a uniform paste slurry with a slump of 180-220mm. S5. Pump the paste slurry into the goaf and let it sit naturally for curing.

5. The method for preparing the low-temperature antifreeze coal mine paste filling material according to claim 4, characterized in that, In step S4, the stirring speed is 800-1000 r / min.

6. The method for preparing the low-temperature antifreeze coal mine paste filling material according to claim 4, characterized in that, In step S3, the low-speed stirring speed is 200-300 r / min, and the stirring time is 2-4 min.